Subtitling as a pedagogical tool for language teaching in journalism - Villela, Lucinea Marcelino [UNESP] (Canadian Center of Science and Education, 2014)
This study was designed to present and discuss some results produced by a research involving the use of English subtitles of some news videos from the webiste Reuters.com (http://www.reuters.com) with pedagogical reasons in a Brazilian context (Academic English for Journalism). We have developed the research during two semesters at UNESP (Universidade Estadual Paulista Júlio de Mesquita Filho). The professor in charge of the study has chosen the students of Journalism as the audience to whom the videos were presented. The assumptions of many theorists and experts in Audiovisual Translation were adopted as our Theoretical Sources. The first step of the study was the assessment of the syllabus of each course. This was very helpful as a guidance in order to choose the most relevant and interesting videos for students. After the evaluation of academic and professional interests, we chose some videos to insert appropriate subtitles, according to some strategies suggested by Panayota Georgakopoulou and Henrik Gottlieb. Finally we presented the videos during the English classes. At the first time, they were presented without subtitles just to notice the comprehension level of the students. After that, the videos were presented with English subtitles. As we first assumed, the students haven’t had the whole comprehension of specific details during the first presentation, they have just used their previous knowledge and the visual aids to help them in a superficial understanding of the news. As the subtitles appear, the process of communication was finally accomplished.
Keywords: Audiovisual translation; English teaching; Reuters; Subtitling; Translation studies; Jornalismo; Comunicação; Ensino de Língua Inglesa; Legendagem